Pathology of surgically remediable epilepsy: How to evaluate - Rajalakshmi Poyuran (Wolters Kluwer Medknow Publications, 2022)
Epilepsy surgery is a well-established treatment modality in selected cases of medically refractory epilepsy. Advances in neuroimaging technology has greatly facilitated detection of lesions that are surgically amenable. Hippocampal sclerosis is the most common pathology encountered among specimens from epilepsy-related surgeries. Other common pathologies are malformations of cortical development including focal cortical dysplasia, neoplasms, vascular malformations, inflammatory conditions including Rasmussen encephalitis and glial scars. Proper handling of surgical specimens is necessary for microscopic evaluation. Accurate interpretation and classification of lesions will help define clinically relevant etiologies. In this review, neuropathological aspects of the common etiologies underlying drug-resistant epilepsies are discussed.